PRONATION POSITION OF OXYGEN SATURATION, RESPIRATORY AND PULSE FREQUENCY IN LOW BIRTH WEIGHT BABIES (STIKes Mitra Keluarga, 2021)
Introduction: Data from WHO 2018 shows the prevalence of LBW is estimated at 21% globally with a limit of 4.5%-40%. LBW babies often have complications in the form of Respiratory Distress Syndrome and an increase in pulse rate. One way to prevent complications is to place the baby in a prone position. Based on scientific article searches, this literature review aims to determine the effect of pronation position on oxygen saturation, pulse rate, and respiratory rate in LBW infants. Method: The type of research was a Literature Review with meta-analysis. Journal searches are carried out on the electronic basis of Google Scholar, Garuda Portal, One Search, and Pubmed, totaling 30 articles. The literature used is literature published from 2016 - 2021. Results: The study results of 30 articles found that the average oxygen saturation before and after being given a pronation position was in the range of 90.27% - 98.1%. The average pulse frequency before and after being given a pronation position was in the range of 144.87 x/minute -140.90 x/minute. The average breathing frequency before and after being given a pronation position was in the range of 69.50 x/minute – 44.18 x/minute. All articles have the effect of pronation position on oxygen saturation in infants (LBW). There is an effect of pronation position on oxygen saturation, respiratory, and pulse with p-value <0,05. Conclusion: It was concluded that the pronation position affected the oxygen saturation, pulse rate, and respiratory frequency in LBW infants. It is expected for nursing services to make the provision of a pronation position as one of the nursing interventions and become a standard operating procedure in the management of LBW infants.